Non-extractable residues (NER) in persistence assessment: effect on the degradation half-life of chemicals - Cindy Jespersen; Stefan Trapp; Matthias Kästner (Environmental Sciences Europe)
Abstract The ECHA guidance on persistence (P) assessment has been updated with respect to non-extractable residues (NER). Unless further characterized, total NER shall be considered as non-degraded parent compound. We investigated how different NER fractions affect degradation half-lives (DegT50) of chemicals and the P assessment. Total NER consist of the fractions sorbed/sequestered (NER I), covalently bound (NER II), and bioNER (incorporated into the biomass, NER III). NER I pose a risk due to potential release, NER II have much lower release potential, and bioNER do not have any. NER I and NER II are considered as xenoNER. Data from 46 degradation tests with 24 substances were analyzed to find DegT50 for four scenarios: (i) extractable parent compound, (ii) parent plus total NER, (iii) parent plus xenoNER, and (iv) parent plus NER I. The microbial turnover to biomass (MTB) model was applied to calculate bioNER, and then xenoNER were calculated as total NER minus bioNER. The half-lives were determined by the fit program CAKE, using single first-order kinetics (SFO) for all fits. We found increasing degradation half-lives for the scenarios: extractable parent only < parent + NER I < parent + xenoNER < parent + total NER. A third of all chemicals show half-lives above the persistence criterion (120 days in OECD 307 and 308, and 40 days in OECD 309) for scenario i, and two thirds with scenario ii and, therefore, would be classified as ‘persistent’. For two compounds, the subtraction of bioNER led to a change to ‘not persistent’. The inclusion of NER in the P assessment (ECHA 2017, 2023) will thus have significant effects on the DegT50 of compounds and the persistence assessment. Experimental quantification of NER I (scenario iv) significantly reduces half-lives, in comparison to total NER (scenario ii). The results are closer to half-lives for parent only (scenario i) and give the lowest acceptable DegT50 below the vP criteria under the latest guidance. In addition, refining the DegT50 based on modelled bioNER can provide a more realistic option for persistence assessment, without laborious and costly analyses for NER I determination, when considered in the regulatory assessment of persistence. Moreover, bioNER can also be calculated for existing test data.